2006
DOI: 10.1097/01.smj.0000240161.25700.b0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Benign Nonparasitic Hepatic Cysts: A Prospective Nonrandomized Study

Abstract: Laparoscopic management of congenital hepatic cysts has become the new gold standard, associated with minimum morbidity and good long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
3
8
0
4
Order By: Relevance
“…Giant liver cysts are found almost exclusively in women over fifty y of age [2]. The majority of our patients were female (83%) with a mean age of 59.2 y, a finding which correlates with many other studies [2,5,6,10,11,14], except Palanivelu et al [13], who found that 81% of patients were male.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Giant liver cysts are found almost exclusively in women over fifty y of age [2]. The majority of our patients were female (83%) with a mean age of 59.2 y, a finding which correlates with many other studies [2,5,6,10,11,14], except Palanivelu et al [13], who found that 81% of patients were male.…”
Section: Discussionsupporting
confidence: 88%
“…Most liver cysts are asymptomatic; however, when they do become symptomatic, the most common presenting symptom in most studies, including the present study, is abdominal pain [3,6,10,13,14]. Giant liver cysts are found almost exclusively in women over fifty y of age [2].…”
Section: Discussionmentioning
confidence: 99%
“…Our operative time remains in the interval time reported in the literature during multitrocar laparoscopic liver cyst unroofing 11,23 and comparable to the 60–100 minutes reported during SAL. 5,17-18,20 …”
Section: Discussionsupporting
confidence: 79%
“…The harmonic scalpel is used in many different operations, including cholecystectomy [2,5,8] , appendectomy [2,9] , fenestration of abdominal cysts [2,10] , reflux esophagitis procedures [11] , large bowel operations [12][13][14] , stomach resection [15][16][17] , liver resection [18] , splenectomy [19] , and fenestration of non-parasitic spleen and liver cysts [20][21][22] . Recently, the harmonic scalpel has been used in transanal endoscopic microsurgery [23][24][25] , endoscopic inguinal and abdominal wall hernia operations [2,26,27] , and hemorrhoidectomy [28] .…”
Section: Introductionmentioning
confidence: 99%